Engaging Empowered Mothering: Black Caribbean Diasporic (M)othering Under Patriarchal Motherhood - Beatson, Erica (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
Women living in Diaspora are presented with different conflicts under patriarchal motherhood. The work of Zadie Smith, in her novel White Teeth, depicts racialized women struggling with their identities as mothers while negotiating their experiences from being mothered in a different culture and how to mother for a “new” nation. Smith depicts women who have migrated from Bangladesh and the Caribbean, and take up their roles as mothers in England. This cross-cultural shift, in turn, shapes how they feel about themselves as mothers. This is not to say that these women are disempowered; rather, there are moments of isolation in their practice as mothers, which facilitate empowerment. While the boundaries of patriarchal motherhood limit mothers’ authority in their roles, this paper argues that these boundaries present unique challenges for women living in Diaspora. This paper will look at Diasporic women’s navigation of the patriarchal institution of motherhood. Diaspora is experienced differently on the basis of gender, racial identity, class, and nationhood. This paper utilizes a feminist mothering theoretical lens under which empowered mothering is recognized as an alternate location for resistance to occur.